How Does the Rib Cage Affect the Biomechanical Properties of the Thoracic Spine? A Systematic Literature Review - Liebsch, Christian; Wilke, Hans-Joachim (Frontiers in Bioengineering and Biotechnology, 2022)
The vast majority of previous experimental studies on the thoracic spine were performed without the entire rib cage, while significant contributive aspects regrading stability and motion behavior were shown in several other studies. The aim of this literature review was to pool and increase evidence on the effect of the rib cage on human thoracic spinal biomechanical characteristics by collating and interrelating previous experimental findings in order to support interpretations of in vitro and in silico studies disregarding the rib cage, to create comparability and reproducibility for all studies including the rib cage, and to provide combined comparative data for future biomechanical studies on the thoracic spine. After systematic literature search corresponding to PRISMA guidelines, eleven studies were included and quantitatively evaluated in this review. Combined data exhibited that the rib cage increases thoracic spinal stability in all motion planes, primarily in axial rotation and predominantly in the upper thorax half, reducing thoracic spinal range of motion, neutral zone, and intradiscal pressure, while increasing thoracic spinal neutral and elastic zone stiffness, compression resistance, and, in neutral position, the intradiscal pressure. In particular, the costosternal connection was found to be the primary stabilizer and an essential determinant for the kinematics of the overall thoracic spine, while the costotransverse and costovertebral joints predominantly reinforce the stability of the single thoracic spinal segments but do not alter thoracic spinal kinematics. Neutral zone and neutral zone stiffness were more affected by rib cage removal compared to range of motion and elastic zone stiffness, thus also representing essential parameters for destabilization of the thoracic spine. As a result, rib cage and thoracic spine form a biomechanical entity that should not be separated. Therefore, usage of entire human non-degenerated thoracic spine and rib cage specimens together with pure moment application and sagittal curvature determination is recommended for future in vitro testing in order to ensure comparability, reproducibility, and quasi-physiological validity.